Digital Soft Power of Malaysia in ASEAN: The #VisitMalaysia2026 Instagram Campaign - Husna Nur Amalina (Universitas Merdeka Malang, 2026)
This study explores how Malaysia applies digital soft power within the ASEAN region through used the #VisitMalaysia2026 campaign on Instagram. Using a qualitative descriptive and content analysis, this reseach shows how cultural narratives are represented in posts shared by @tourismmalaysia on Instagram. The analysis highlights three dominant themes: cultural heritage diversity, tourism economy a regional connectivity and environtmental and sustainable tourism. Engagement data show that modern tourism attractions (e.g., Tuah 1895 Viewing Deck) generate the highest visibility, while cultural content (e.g. Deepavali Festival and Sri Maha Mariamman Temple) achieves strong interactive engagement, reinforcing Malaysia’s multicultural identity. Nature-based content further strengthens Malaysia’s sustainable diplomacy narrative. Overall, the #VisitMalaysia2026 campaign demonstrates how Instagram functions as a digital soft power tool, amplifying Malaysia’s cultural appeal, economic positioning and environmental values across ASEAN.